IMPLEMENTASIPERMAINAN EDUKATIF BARANG BEKAS DALAM MENGEMBANGKAN MOTORIK KASAR ANAK USIA DINI DI PAUDAR-ROHIM DESA SUMBERBENING KECAMATAN BRINGIN KABUPATEN NGAWI - Ucik Hidayah Binsa; Suci Ayu Lestari (Kurikula : Jurnal Pendidikan, 2021)
ABSTRACT Utilization and management of used goods is a mindset of advanced and modern society, because an advanced civilization is a civilization that has an awareness of simplicity, thrift, effectiveness, convenience for sustainable survival. The approach taken in this research is qualitative. A qualitative approach is a research procedure that produces descriptive data in the form of written or spoken words from people whose behavior can be observed. Efforts to develop gross motor skills in early childhood using used media in a lesson can improve gross motor skills in children. The development experienced by children is indicated by several things that can be seen, including increasingly flexible movements, being able to make works from used goods that will be used for playing and moving quickly when collecting used goods to be used in games. Teaching and learning activities for children at PAUD Ar-Rohim Sumberbening, Bringin Ngawi which were carried out with a traditional game of engkleng and jumping rope and playing by avoiding used bottles in a zigzag and continuous manner in an effort to improve and develop children's gross motor skills were successful. These indications can be seen clearly from the movements of children who are increasingly flexible and enthusiastic in doing so and their movements are appropriate and correct according to the instructions given. Key Words: Educational Games, Secondhand,